Kebijakan Pembangunan Berkelanjutan Desa: Langkah Strategis Pemenuhan SDGs Desa - Assajid, Sulthan; Khoiron, Khoiron; Wulan Sekarsari, Retno (Jurnal Ilmiah Administrasi Publik, 2024)
The village development paradigm changed along with the implementation of Law number. 6 of 2014 brings villages as subjects and objects of development simultaneously. This condition means that villages need clear goals in their development, along with this problem the Village SDGs provide direction for achieving sustainable development. Landungsari Village as a village that is categorized as an independent village with an IDM of 0.8879/1.0000 has a Village SDGs achievement of 40.53/100.00 leaving a question about what village policies are in sustainable development of the village. This research aims to explain the development policies launched in Landungsari Village, as the Village SDGs are the direction of village development. This research uses a descriptive qualitative method with a focus on development policies in Landungsari Village, where the data analysis process uses the data triangulation method. Primary data was taken through interviews, observation and analysis of village government documents, and secondary data came from scientific papers relevant to the research. In this research, it was found that village development policies have led to the fulfillment of Village SDGs, but village development policies are not yet fully sustainable, this is because there is no serious policy in environmental conservation to create sustainability into the future.